Isosexual precocity in girls - M. Suttan Assin (Paediatrica Indonesiana, 1984)
Puberty is considered precocious when the onset takes place prior to eight years of age. lsosexual precocious puberty indicates that sexual development has occurred appropriate io the individual's phenotype. This can be a) true sexual or b) pseudosexual. In true sexual precocity there is a premature activation of hypothalamic-pituitary axis, while pseudosexual precocity is due to disease of the gonads or adrenal glands or, rarely, other hormone producing tissues. Incomplete sexual development can be ''premature thelarche'' or "premature pubarche". We have encountered 13 cases of precocious puberty in girls in 10 years time (1971 - 1980). Eight of them were idiopathic. Diagnostic procedures, medical treatment and psychosocial handling are discussed in this paper.